Effects of Amino Acid Ratios and Lysine Level on Nursery Pig Growth Performance - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband; K. J. Touchette (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 2,268 pigs (PIC 327 × L42, initially 16.2 lb BW) was used in a 28-d growth study with 54 pigs per feeder (experimental unit) and 6 replications per treatment. Pigs were randomly allotted to pens at weaning and fed a common starter diet for 8 d. Pens were then blocked by BW and allotted to 1 of 7 dietary treatments in a randomized complete block design. Treatments were arranged in two levels of standardized ileal digestible (SID) Lys (low,1.25% and high, 1.35%) and SID amino acid (AA) ratios relative to Lys (industry, 95% of maximum performance, and maximum performance). The seventh dietary treatment was a control diet (1.35% SID Lys). Industry ratios were 55% Met+Cys:Lys, 62% Thr:Lys, 18% Trp:Lys, and 65% Val:Lys. Maximum diet ratios were 60% Met+Cys:Lys, 65% Thr:Lys, 21% Trp:Lys, and 72% Val:Lys. The 95% ratios were formulated to target 95% of maximum performance and were 56% Met+Cys:Lys, 62% Thr:Lys, 19% Trp:Lys, and 67% Val:Lys. Diets were formulated to meet or exceed the Ile requirement with feed-grade Lys, Met, Thr, Trp, and Val added. The control diet contained less feed-grade AA (0.39% L-Lys HCl vs. 0.50 to 0.55% in other diets) and 5% enzymatically-processed soybean meal to achieve a similar conventional soybean meal level to the high SID Lys diets. Experimental diets were formulated using analyzed total AA for corn, soybean meal, and dried distillers grains with solubles and fed for 14 d in meal form. A post-treatment period with a common diet was fed from d 14 to 28. From d 0 to 14, feeding high Lys diets increased (P<0.001) ADG and F/G compared with low Lys diets with no evidence for differences in ADFI. For ADG and F/G, pigs fed maximum AA ratios had improved (P<0.05) performance compared to those fed industry ratios at low Lys, but not at high Lys levels. In conclusion, high AA ratios were more critical in diets formulated below the Lys requirement of the pig.
Keywords: amino acid ratios; lysine; nursery pig